Driving SMES towards Green Business: The Impact of Sustainable Marketing Mix on Performance and Loyalty in BNI'S Go Green Movement - Rosalinda , Chichi; Idris, Idris; Susanto, Perengki (Journal of Ecohumanism, 2024)
Growing global concerns over environmental issues, such as climate change and pollution, have heightened the demand for sustainable business practices, particularly in the banking sector. Financial institutions support environmental sustainability through green finance by offering eco-friendly products like green loans and bonds. This study examines how BNI's Go-Green initiative enhances SME customer loyalty by incorporating the sustainable marketing mix, focusing on people, profit, and planet. A quantitative approach was used to assess the impact of the sustainable marketing mix on SME performance and customer loyalty within BNI's Go Green movement in Bukittinggi, Indonesia. A stratified random sample of 303 SMEs was selected from a population of 1,239. Data were gathered through structured questionnaires using a five-point Likert scale and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Confirmatory Factor Analysis (CFA) validated the measurement model, and the structural model assessed direct and indirect effects. The variable had the highest Average Variance Extracted (AVE) 0.873. Discriminant validity showed a strong correlation between business sustainability and customer loyalty (0.768). Place and Business Sustainability had significant positive effects on customer loyalty, while People and Planet had more limited impacts. This study introduces the expanded marketing mix people, profit, and planet into the green finance framework and highlights the underexplored mediating role of business sustainability in fostering SME customer loyalty. The findings emphasize the importance of aligning green banking products with SME needs to enhance loyalty and support global sustainability goals, including the United Nations’ Sustainable Development Goals (SDGs).